Mena Lafkioui. 2007. Atlas linguistique des variétés berbères - Souag, Lameen (Afrikanistik online, 2007)
In the mountainous landscape of northeastern Morocco, a fairly large geographically contiguous Berber-speaking area with a few million inhabitants is to be found, called the Rif. Its people are generally described as speaking a single Zenati Northern Berber language, Tarifit, apart from in its southwestern corner, where another non-Zenati Northern Berber language, Senhaji, may be distinguished. While such a description is well-founded as far as it goes, it often represents a great oversimplification, as Mena Lafkioui's work reveals. Historical linguists looking at innovations within Berber, typologists examining diversity, syntacticians looking at microvariation, anthropologists seeking to trace migrations - all will benefit greatly from this work, which makes it both possible and imperative to resist the temptation to say “Tarifit does so-and-so” in favour of a more nuanced account of variation within the Rif. Even many elements commonly thought of as characteristic of the Rif, such as the sound change l > r, are revealed to be in truth characteristics of a particular central area within the Rif, with older forms still conserved along the outskirts, or to be just a particular case within a large array of forms.
Keywords: Berber; Morocco; Rif